Răspuns :
(-√2 + 5)^2 +2(-√2 - 4)(-√2 + 5) +(-√2 - 4)^2
....................................................................
[tex]\it(-\sqrt2+5)^2+2(-\sqrt2-4)(-\sqrt2+5)+(-\sqrt2-4)^2 = [/tex]
[tex] =(\it5- \sqrt{\it 2}\it )^2 - \it2(\sqrt2+4)(5-\sqrt2) + (\sqrt2+4)^2=[/tex]
[tex] =(\it5-\sqrt2-\sqrt2-4)^2=(1-2\sqrt2)^2=[/tex]
[tex]=\it1-4\sqrt2+8=9-4\sqrt2 [/tex]
....................................................................
[tex]\it(-\sqrt2+5)^2+2(-\sqrt2-4)(-\sqrt2+5)+(-\sqrt2-4)^2 = [/tex]
[tex] =(\it5- \sqrt{\it 2}\it )^2 - \it2(\sqrt2+4)(5-\sqrt2) + (\sqrt2+4)^2=[/tex]
[tex] =(\it5-\sqrt2-\sqrt2-4)^2=(1-2\sqrt2)^2=[/tex]
[tex]=\it1-4\sqrt2+8=9-4\sqrt2 [/tex]
[tex](-\sqrt{2}+5)^2+2(-\sqrt{2}-4)(-\sqrt{2}+5)+ (-\sqrt{2}-4)^2= \\\\\\ = [(-\sqrt{2}+5)+(-\sqrt{2}-4)]^2= \\\\= ( -2\sqrt{2}+1)^2= \\\\ = 8-4\sqrt{2}+1= \\\\ \underline{=9-4\sqrt{2}}[/tex]